Cognitive interviewing: lessons learned and recommendations for structured interviews with survivors of crime - Houston-Kolnik, Jaclyn D. (Journal of family violence, 2022)
This article explores the use of cognitive interviewing among one sensitive population, survivors of crime, and shares lessons learned from a cognitive interviewing study of LGBTQ+ survivors of crime. Cognitive interviewing is a structured research method that assists researchers in designing survey questions that clearly and accurately operationalize construct(s) of interest for use with one or more sub-populations. This method may be particularly important when conducting research on sensitive topics or with survivors who have experienced marginalization, oppression, or stigmatization because specific language or phrases may be confusing or not reflected among tools validated with mainstream dominant populations. However, past research on survivor-centered interviewing has raised questions about how these structured research methods can attend to survivor choice and autonomy. Researchers critically reflect on their experiences conducting cognitive interviews with LGBTQ+ survivors of crime and examine their processes and protocols in light of survivor-centered interview practices. Recommendations on how to use structured methods with sensitive populations are also provided to inform future research.